Transitivity choices in an abridged text: The case of a graphic novel - Thusha Rani Rajendra (Universitas Syiah Kuala, 2020)
This article investigates the application of Halliday's theory of transitivity to analyse the verbal structures of an abridged text in the form of a graphic novel. Having been condensed from the original classic Journey to the Centre of the Earth (JttCotE) by Jules Verne, the present study examines the link between these structures and how they represent the original text. The focus of the analysis concentrates on the verbal text contained in speech bubbles and caption boxes; common characteristics of the comics medium.  Based on the Systemic Functional Linguistics (SFL) framework of the ideational metafunction, this article discusses how linguistic formations are constructed and construed through transitivity in an abridged text. In addition, the analysis also looks into how the authors have adapted the original text into a graphic novel through the adoption of a few specific Processes. As such an exploration is limited, the current study fills the gap in this area.  The analysis of data indicates that careful employment of linguistic choices forms the core of the novel which inherently is also supported through its visual representations. The results reveal that Material Processes are the most prominent in this adapted version of the novel, followed by Relational and Behavioural Processes respectively. This study highlights how linguistic choices support the original text, though an abridged version, specifically in the panels of Journey to the Centre of the Earth. The findings can serve to understand how authors construct their versions of abridged texts to adhere to the original text.